'Like' if you support refugees: preservice teachers' sensemaking of contested issues in a digitally-mediated multicultural education course. (3rd July 2017) - Deroo, Matthew R.; Farver, Scott D.; Dunn, Alyssa Hadley
Abstract: The advent of Web 2.0 and social media have changed how individuals act and react in mediated spaces. Pre-service teachers, familiar with navigating online spaces, enter their courses with a wealth of digital experiences, understandings and ways of making meaning. This study examines how pre-service teachers in a multicultural education course communicate across digitally mediated spaces. Using discourse analysis and sensemaking theory to analyse their Facebook posts, we asked: How do White pre-service teachers discuss and make sense of issues related to immigration in a multicultural education course? Our findings revealed that participants attempted to make sense of immigrant language and culture while building new knowledge and identities as future educators at a time when public narratives about immigrants were disparaging. Further, blended learning provided a beneficial digital space for pre-service teachers' sensemaking processes. Implications are offered for research and practice.